Specific inhibition of carbonic anhydrase IX activity enhances the in vivo therapeutic effect of tumor irradiation. - Dubois, L; Peeters, S; Lieuwes, N; Geusens, N; Thiry, A; Wigfield, S; Carta, F; McIntyre, A; Scozzafava, A; Dogné, J; Supuran, C; Harris, A; et al. (2011)
BACKGROUND AND PURPOSE: Carbonic anhydrase (CA) IX expression is increased upon hypoxia and has been proposed as a therapeutic target since it has been associated with poor prognosis, tumor progression and pH regulation. The aim of this study was to evaluate the antitumor activity of a high CAIX-affinity indanesulfonamide (11c) combined with irradiation, compared with the general CA inhibitor acetazolamide (AZA). MATERIAL AND METHODS: HT-29 carcinoma cells with or without (genetic knockdown, KD) CAIX expression were incubated with 11c/AZA under different oxygen levels and proliferation, apoptosis and radiosensitivity were evaluated. 11c/AZA was administered intravenously (1×/day; 5 days) to tumor-bearing mice and tumor irradiation (10 Gy) was performed at day 3 of the injection period. Tumor growth and potential treatment toxicity were monitored (3×/week). RESULTS: Treatment with 11c/AZA alone resulted in tumor regression, which was further increased in CAIX expressing cells by combining 11c with irradiation. AZA demonstrated also an additional effect in the KD tumors when combined with irradiation. CAIX inhibition in vitro significantly reduced proliferation and increased apoptosis upon hypoxia exposure without affecting intrinsic radiosensitivity. CONCLUSIONS: Specific inhibition of CAIX activity enhanced the effect of tumor irradiation and might, therefore, be an attractive strategy to improve overall cancer treatment.